Flora of Brazil: Elaeocarpaceae - Sampaio, Daniela [UNESP] (FapUNIFESP (SciELO), 2020)
The major objective of this study was to contribute to the Flora of Brazil 2020, which is part of the targets established by the Conference of the Parties of the Convention’s signatory countries on Biological Diversity. The development of the Brazilian Flora is coordinated by the Rio de Janeiro Botanical Garden, under the direction of the Ministry of Environment of Brazil and involves national and international research institutions. In this work a floristic survey of the species of Elaeocarpaceae that occur in Brazil was made, as well as the elaboration of a flora for the family, with identification keys, descriptions of genera and species, taxonomic comments and geographical distribution. The main national herbaria were consulted and analyzed, either in person or through loans. The nomenclature types deposited in national and foreign herbaria were analyzed. Two genera were recognized: Crinodendron with one species and Sloanea with 43. Thus, 44 valid names, 57 synonyms and one new species for the family in Brazil were recognized. In addition, seven lectotypes, and 16 new synonyms were assigned.
Flora do Brasil: Elaeocarpaceae
Keywords: Brazilian flora; Crinodendron; Sloanea; World flora